2014
DOI: 10.3389/fphys.2014.00328
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial dysfunction as a nexus for endothelial cell-cardiomyocyte miscommunication

Abstract: Most studies of the heart focus on cardiomyocytes (CM) at the exclusion of other cell types such as myocardial endothelial cells (EC). Such mono-cellular approaches propagate the presumption that EC provide a mere “passive lining” or supportive role. In fact, EC contribute to a dynamic network regulating vascular tone, cardiac development, and repair. Two distinct EC types, vascular EC and epicardial EC, possess important structural and signaling properties within both the healthy and diseased myocardium. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 90 publications
0
25
0
1
Order By: Relevance
“…Previous data indicate that abnormal cross‐talk between endothelial cells and cardiomyocytes plays an important role in the pathogenesis of heart failure (Tirziu et al . ; Leucker & Jones, ) and cardiac hypertrophy (Tirziu & Simons, ). Alternatively, our findings may represent the effect of an endothelium‐specific mechanism including augmented coronary microvascular function in the setting of pressure overload and/or an attenuation of another proposed mechanism underling cardiac fibrosis, such as endothelial to mesenchymal transition (Zeisberg et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous data indicate that abnormal cross‐talk between endothelial cells and cardiomyocytes plays an important role in the pathogenesis of heart failure (Tirziu et al . ; Leucker & Jones, ) and cardiac hypertrophy (Tirziu & Simons, ). Alternatively, our findings may represent the effect of an endothelium‐specific mechanism including augmented coronary microvascular function in the setting of pressure overload and/or an attenuation of another proposed mechanism underling cardiac fibrosis, such as endothelial to mesenchymal transition (Zeisberg et al .…”
Section: Discussionmentioning
confidence: 99%
“…It is known that normal endothelial function is critical for the regulation of cardiac function and that impaired endothelial function can lead to abnormalities in cardiac contractility, cardiomyocyte proliferation/apoptosis and cardiac hypertrophy (Chin‐Dusting et al . ; Leucker & Jones, ; Mordi & Tzemos, ; McCormick et al . ).…”
Section: Introductionmentioning
confidence: 99%
“…Endothelial cells are covered by surface proteoglycans that form part of the barrier functions of the blood-tissue interface [128]. Endothelial cells are a main cell type in the vasculature and contribute to the maintenance of vascular tone and cardiac repair [129]. Vascular leaks of fluid from the plasma to the interstitial space contribute to inflammation and myocardial dysfunction.…”
Section: Endothelial Dysfunctionmentioning
confidence: 99%
“…These excessive ROS such as superoxide can react with NO to form peroxynitrite (ONOO − ) [45], thereby reducing the available NO level for proper endothelial function. Thus, high ROS generation may lead to different abnormalities including endothelial dysfunction [46,47]. Findings from this study showed 8-OHdG, a marker for oxidative stress to signi cantly increase with increasing quartiles of ADMA and also positively correlated with ADMA.…”
Section: Discussionmentioning
confidence: 65%